Yin and Yang of skin microbiota in "swimmer acne". Issue 6 (17th February 2022) - Morss‐Walton, Peyton C.; McGee, Jean S.; Rosales Santillan, Monica; Kimball, Ranch; Cukras, Anthony; Patwardhan, Sachin V.; Porter, Martina L.; Kimball, Alexa B.
Abstract: Cutibacterium acnes ( C. acnes ) is an organism implicated in the pathogenesis of acne. Despite regular immersion in antimicrobial chlorine, adolescent swimmers suffer from acne and tend to be resistant to standard therapies. Given the presence of Pseudomonas within swimming facilities, we hypothesized that "swimmer acne" is potentially driven by a different microbial mechanism. In this study, we aimed to examine the microbial dynamics of C. acnes and Pseudomonadaceae, a family of gram‐negative bacteria (includes Pseudomonas aeruginosa ), in swimmers and its potential contribution to the pathogenesis of acne in this population. Using fluorescence photography that measures the Coproporphyrin III (CPIII), we quantitated an absolute abundance of C. acnes present on the face of each participant pre‐ and post‐swimming. In addition, 16S rRNA gene sequencing was utilized to assess relative abundance of the skin microbiota on each participant pre‐ and post‐swimming. 16 swimmers (8 girls and 8 boys) completed the study. Seven had acne on the face. The CPIII fluorescence levels decreased for all swimmers after 1 h of swimming ( p ‐value <0.001). In contrast, the relative abundance of C. acnes remained unchanged, while that of Pseudomonadaceae increased after swimming ( p ‐value =0.027). Comparing the relative abundances of Pseudomonadaceae before swimming, there was a significant increase in variance from the mean in acne group as compared to no acne group ( p ‐value <0.001). Taken together, we conclude that the skin dysbiosis resulting from repeated decolonization and colonization of C . acnes and Pseudomonadaceae, respectively, can potentially be associated with the pathogenesis of acne in swimmers.